The Complete Book of Bible Trivia - J. Stephen Lang (USA Tyndale House, 1996)
Contains more than 4,500 questions and answers about the Bible and the people, places, and events described in it.
Keywords: Holy Bible: General (3GdcJGH GdebOS(B: (3YehejGJs; Bible